Tracking of intertissue migration reveals the origins of tumor-infiltrating monocytes - Shand, Francis H W; Ueha, Satoshi; Otsuji, Mikiya; Koid, Suang Suang; Shichino, Shigeyuki; Tsukui, Tatsuya; Kosugi-Kanaya, Mizuha; Abe, Jun; Tomura, Michio; Ziogas, James; Matsushima, Kouji (Proceedings of the National Academy of Sciences - PNAS, 2014)
Myeloid cells such as monocytes and monocyte-derived macrophages promote tumor progression. Recent reports suggest that extramedullary hematopoiesis sustains a sizable reservoir of tumor-infiltrating monocytes in the spleen. However, the influence of the spleen on tumor development and the extent to which spleen monocytes populate the tumor relative to bone marrow (BM) monocytes remain controversial. Here, we used mice expressing the photoconvertible protein Kikume Green-Red to track the redistribution of monocytes from the BM and spleen, and mice expressing fluorescent ubiquitination-based cell-cycle indicator proteins to monitor active hematopoiesis in these tissues. In mice bearing late-stage tumors, the BM, besides being the major site of monocyte production, supplied the expansion of the spleen reservoir, replacing 9% of spleen monocytes every hour. Deployment of monocytes was equally rapid from the BM and the spleen. However, BM monocytes were younger than those in the spleen and were 2.7 times more likely to migrate into the tumor from the circulation. Partly as a result of this intrinsic difference in migration potential, spleen monocytes made only a minor contribution to the tumor-infiltrating monocyte population. At least 27% of tumor monocytes had traveled from the BM in the last 24 h, compared with only 2% from the spleen. These observations highlight the importance of the BM as the primary hematopoietic tissue and monocyte reservoir in tumor-bearing mice, despite the changes that occur in the spleen monocyte reservoir during tumor development.